AKOMODASI KOMUNIKASI DALAM INTERAKSI ANTARBUDAYA PEDAGANG ETNIS BUGIS DAN MINANG KABAU DI PASAR INDUK TALANG BANJAR JAMBI - Riandy F, Andre; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Talang Banjar Central Market Jambi, is one of the oldest markets in the Jambi city. During the time has never been a major conflict between the existing traders. Minangkabau and Bugis ethnic be the most with 332 and 310 traders. As the two dominant ethnic groups, interaction between Bugis and Minangkabau ethnic are the most frequent cultural communication among others. This research was looking for the adpatation strategies between those ethnic. That strategies can be seen with accomodation of communication theory, with a look at the strategy of convergence, divergence, and the forms of over-accomodation.This study is used Giles’ accomodation of communication theory, used a qualitative research method with symbolic interaction approach. Informants of this study were 7 Bugis ethnic traders and 7 Minangkabau ethnic traders. Then the object is the activities undertaken by the traders that reflect accommodation of communication strategy among Bugis and Minangkabau ethnic. Data collection techniques used are observation, interviews, and documentation. Then to reach the validity of the data in this study, researchers used the extension of participation and triangulation. The results obtained ethnic Bugis and Minangkabau ethnicdo the convergence by using Jambi language and Indonesian languagefor communication, the occasional they use opposite native language with it dialect as well. Adjust the speed of speech.Do touch on the traders manifold same sex.And irrespective of the distance while communicating. At the time of sale communication it goes friendly.Strategy of divergences are with use the native language when talking to traders of different cultures within native dialect also.Whilethe men traders avoid to touch opposite sex of different cultures. As the time of the sale and purchase different roles is very evident.The form of over-accommodation is mostly done by Minangkabau traders to the Bugis traders. it made by Minangkabau ethnic traders are, excessive use of the native language, not heeding the personal identity, joke without looking at the situation, violating personal space, using sounds excessive. While Bugis ethnic traders are using excessive clothing and jewelry.As the time of sale, both of ethnic sometimesdo excessive at the time of bid.Keyword: intercultural interaction, Convergence, Divergence, Form of Over-accomodation.